Threat Existence to Limestone Formations Around Goa Peteng in South Bali Island, Indonesia - Suryana, I Gede Putu Eka; Atmaja, Dewa Made; Pratiwi, Elok Surya; Budiarta, I Gede; Bharata, Ida Bagus Arya Yoga; Wulandari, Ni Ketut Catur; Wulandari, Ni Nyoman Tri (Universitas Negeri Gorontalo, 2024)
The limestone formations are a unit of geological rock formations that are important for the formation of unique Karst Landscapes but are often threatened by development interests, one of which is in the environment around Goa Peteng, whose existence is threatened. This research aims to investigate: 1) the conditions of limestone formations around Goa Peteng, 2) identified threats to the existence of limestone formations around Goa Peteng, and 3) potential opportunities for protecting the existence of limestone formations around Goa Peteng. The methods used in this research include field observation, literature review, and assistance with map digitization. This assistance involves utilizing literature studies, both scientific articles and reports containing maps that also cover the study location. The results of the research show that the limestone formations in the Goa Peteng environment exist at of a level of karst development in the Goa Peteng environment which is Mesokarst and parts of the surrounding area are Non-Karst apart from that there is Exokarst Potential and Endokarst though not much exists at the study location. The real threat to the existence of the karst landscape in the Goa Peteng environment is the development of mass tourism in the form of tourist accommodation such as hotels and villas, which has developed rapidly over the last 14 years, as seen from Satellite Image data. The limestone formations in the Goa Peteng environment themselves has the opportunity to be a place for education and further studies need to be carried out on the limestone formations and karst development in South Bali